Changes in the magnetization hysteresis direction and structure-driven magnetoresistance of a chalcopyrite-based magnetic semiconductor. (23rd February 2016) - Arslanov, T R; Kilanski, L; López-Moreno, S; Mollaev, A Yu; Arslanov, R K; Fedorchenko, I V; Chatterji, T; Marenkin, S F; Emirov, R M
Abstract: An unusual change in the hysteresis direction is believed as rare phenomenon associated with perovskite-type structure. Such 'anomalous' magnetization hysteresis could possess a direct impact on the giant magnetoresistance (MR). Here we demonstrate that the room-temperature magnetization versus pressure for chalcopyrite semiconductor Zn1− x Mn x GeAs2 with x   =  0.01 follows a usual direction of hysteresis, while the direction turns into anomalous for x   =  0.07. Both these phenomena are results of a pressure-induced structural transition occurring in the host material, as is evident from volumetric measurements and ab initio calculations. This structural transition gives rise to the pressure-enhanced large MR and changes it drastically. Unlike the case of x   =  0.01 where MR can be well reproduced within a theoretical approach, the presence of magnetic inhomogeneities for x   =  0.07 induces an unexpected crossover from large positive to non-saturating negative MR (~92% at H   =  5 kOe) in the new high-pressure phase. These results suggest that Zn1− x Mn x GeAs2 provides an example of a chalcopyrite-based material whose functional possibilities could be expanded through a new type of 'structure-driven' MR.